Supervised Internship in the Rural Education License course: reflections about teaching practice - Jorge Luis D'Ávila (Universidade Federal do Norte do Tocantins, 2021)
The purpose of the text is to report the experiences obtained in the supervised internship carried out by the students of the first group of graduates of the Degree in Rural Education (LEDUCAMPO) course, which was offered by the Federal University of Mato Grosso do Sul (UFMS), developed in the schools of the different municipalities in the state of Mato Grosso do Sul (MS). Bibliographic research was carried out with qualitative approaches that argue about the supervised internship in school education as well as, analysis of reports, lesson plans organized by LEDUCAMPO academics during the period of the supervised internship, evaluations carried out by the supervising teachers, in addition to the documents produced in the UFMS that legitimize the internship process. The centrality of the internship in rural education must be anchored in the assumptions of teacher preparation that makes the academic understand that the public school is exclusionary, marginalized and guided by the dominant ideology that seeks training to meet the demands of the labor market, contrary to this, the academic must promote a humanistic and progressive education.